2020
DOI: 10.1002/lary.28866
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sentinel Lymph Node Biopsy and LVI on Merkel Cell Carcinoma Prognosis and Treatment

Abstract: Objective Prognostic factors and optimal treatment approaches for Merkel cell carcinoma (MCC) remain uncertain. This study evaluated the influences of sentinel lymph node (SLN) biopsy and lymphovascular invasion (LVI) on treatment planning and prognosis. Study Design Retrospective cohort study. Methods Stage 1 to 3 MCC patients treated 2005 to 2018. Predictors of nodal radiation were tested using logistic regression. Predictors of recurrence‐free, disease‐specific, and overall survival were tested in Cox propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 24 publications
0
22
0
2
Order By: Relevance
“…The exact causes of delays in treatment post‐diagnosis are yet to be fully understood, but studies have suggested possible causes ranging from race to socioeconomic status of patients 3,4 . The current standard of care for patients with MCC includes surgical resection, possibly accompanied by sentinel lymph node biopsy and followed by adjuvant radiotherapy and/or systemic therapy, if indicated 5 . Larger studies investigating the elapsed time between patient presentation and receipt of care, and how these durations influence ultimate patient outcomes, are vital in understanding the management of MCC, but are yet to be performed.…”
Section: Introductionmentioning
confidence: 99%
“…The exact causes of delays in treatment post‐diagnosis are yet to be fully understood, but studies have suggested possible causes ranging from race to socioeconomic status of patients 3,4 . The current standard of care for patients with MCC includes surgical resection, possibly accompanied by sentinel lymph node biopsy and followed by adjuvant radiotherapy and/or systemic therapy, if indicated 5 . Larger studies investigating the elapsed time between patient presentation and receipt of care, and how these durations influence ultimate patient outcomes, are vital in understanding the management of MCC, but are yet to be performed.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the literature, occult lymph node disease is present in up to 50% of patients [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]; thus, SLNB should be performed in all patients. We confirmed the value of SLNB by showing that patients with clinically less-suspicious lymph nodes who have not undergone the SLNB had over 5-times higher risk of disease recurrence and nearly 2.5 times higher risk of death.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 50–65% of MCC patients have localized disease at presentation, and 25–50% have regional metastases [ 3 , 4 ]. Subclinical nodal metastases are present in 30–50% of patients with primary MCC, with an increased presence in patients with a primary tumor greater than 1 cm in diameter [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. The sentinel lymph node biopsy (SLNB) is recommended in cases without clinical nodal involvement.…”
Section: Introductionmentioning
confidence: 99%
“…69 A recent retrospective study of 122 patients found that a positive SLNB and lymphovascular invasion were independently associated with worse survival after considering tumor T and node N classification, immunosuppression, age, and the primary site of the tumor. 70 Tumor thickness and size, lymphovascular invasion, immunosuppression, presence of tumor-infiltrating lymphocytes, mitotic rate, and tumor growth pattern have been associated…”
Section: Sentinel Lymph Node Biopsymentioning
confidence: 99%